The Implementation of Muhadhoroh Activities to Improve Public Speaking for Junior High School - agung saputra, nopran riyan; Fajarina, Maskhurin; Af’idah, Syifa’aul’ (Bilingua, 2024)
This study aims to analyze the implementation of the muhadhoroh program in improving students' public speaking skills at Junior High School Ngesong Jombang. The muhadhoroh program involves students giving short talks to their peers regularly. Its goal is to help students develop communication skills, reduce fear or nervousness when speaking, and build confidence. This research used a qualitative case study approach, with data collected through interviews, observations, and documentation. Results show that the muhadhoroh program successfully creates a supportive learning environment that helps students gradually improve their communication skills. Additionally, support from teachers as facilitators plays an important role in the program's success, providing guidance and regular evaluations to help students prepare content and deliver messages effectively. The program also helps develop students' character through topics like moral values, leadership, and social responsibility. This allows students not only to become confident speakers but also to build integrity. The program positively impacts both speakers and the audience, who also benefit by learning from the talks. Overall, muhadhoroh serves as an effective and relevant public speaking model that other schools could use to help students grow into confident individuals with strong communication skills, ready to contribute in social and professional settings.